Firm Productivity and Infrastructure Costs in East Africa - Iimi, Atsushi; Humphrey, Richard Martin; Melibaeva, Sevara (World Bank, Washington, DC, 2015)
Infrastructure is an important driving force for economic growth. It reduces trade and transaction costs and stimulates the productivity of the economy. Africa has been lagging behind in the global manufacturing market. Among others, infrastructure is an important constraint in many African countries. Using firm-level data for East Africa, the paper reexamines the relationship between firm performance and infrastructure. It is shown that labor costs are by far the most important to stimulate firm production. Among the infrastructure sectors, electricity costs have the highest output elasticity, followed by transport costs. In addition, the paper shows that the quality of infrastructure is important to increase firm production. In particular, quality transport infrastructure seems to be essential. The paper also finds that agglomeration economies can reduce firm costs. The agglomeration elasticity is estimated at 0.03–0.04.